1976
DOI: 10.1007/bf00561177
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cells at the sites of vaccinia virus inoculation

Abstract: Langerhans cells in the epidermis at the sites of vaccina virus inoculation were studied with the electron microscope. The cells contained unusually increased numbers of the Langerhans cell granules. Such abnormal Langerhans cells have not been described except for in histiocytosis X. Vaccinia virus particles were found in the Langerhans cells, where they were located individually or embedded in the granular matrix or in lysosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Of note, the i.d. route is the same route used to eradicate smallpox using a very similar virus and possibly via similar mechanisms, since vaccinia virus could be detected in Langerhans cells at the sites of inoculation (36). In vivo presentation of ALVACborne antigens by DCs is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the i.d. route is the same route used to eradicate smallpox using a very similar virus and possibly via similar mechanisms, since vaccinia virus could be detected in Langerhans cells at the sites of inoculation (36). In vivo presentation of ALVACborne antigens by DCs is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculation of a live vaccinia vector into the skin of individuals who lack a functionally normal local immune barrier may lead to disastrous consequences as exemplified by a recent case report [89]. Moreover, infection of Langerhans cells by the vaccinia virus [77] may even accentuate the impairment in Langerhans cell function caused by HIV-1 infection. Such a correlation between decreased number of Langerhans cells in epithelial tissues of AIDS patients and co-infection with opportunistic pathogens has also been demonstrated in oral hairy leukoplakia in AIDS patients [31].…”
mentioning
confidence: 94%
“…They noted the presence of viral particles in Langerhans cells at the site of vaccinia virus inoculation [77]. Later on, Chardonner et al Similarly, it was reported that following infection of the footpad skin of mice with a pathogenic strain of herpes simplex virus-1 (H SV-1), the Langerhans cell density significantly increased [108].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Increase in Langerhans cell density at the site of inoculation was found to correlate with the intrinsic pathogenicity of different vaccinia virus strains [7]. Viral particles were observed in Langerhans cells at the site of vaccinia virus inoculation, suggesting that following internalization of the viral particles, Langerhans cells may process and present vaccinia virus antigens to T cells to stimulate a systemic response to vaccination against smallpox [96].…”
Section: Role Of Dendritic Cells In the Control Of Primary Viral Infementioning
confidence: 93%